Age-related impairment of conducted dilation in human coronary arterioles - Feher, Attila (American Physiological Society, 2014)
Conducted vasodilation is essential to coordinate vascular resistance along distances to ensure adequate tissue perfusion. We hypothesized that conducted vasodilation of coronary resistance arteries declines with age. Coronary arterioles were dissected from right atrial appendage of patients (n = 27) undergoing cardiac surgery. Arterioles (∼100 μm) were cannulated and pressurized (80 mmHg), and developed spontaneous myogenic tone. Conducted vasodilation was initiated by locally administering the endothelium-dependent agonist bradykinin (BK; 100 μM) ejected from a glass micropipette (∼3 μm tip opening, positioned in close proximity to the vessel wall). Diameter changes were measured at local and upstream sites (500 and 1,000 μm from the stimulus) with videomicroscopy. Local administration of BK elicited vasodilation, the magnitude of which increased with the duration of stimulus (69 ± 6, 81 ± 6, 90 ± 2%, after 1, 3, and 5 × 100 ms, respectively). BK-induced dilation remained substantial at upstream sites (500 μm: 53 ± 7%; 1,000 μm: 46 ± 9%). The gap junction uncoupler carbenoxolone or 18-α-glycyrrhetinic acid did not affect local responses, but diminished conducted vasodilation. Inhibitors of small/intermediate conductance calcium-activated potassium channels (SK(Ca)/IK(Ca)), apamin and TRAM34, reduced dilations both at local and remote sites. We found that conducted dilation, but not the local response, was significantly reduced in older (≥64 yr) patients. The nitric oxide (NO) synthesis inhibitor N(ω)-nitro-l-arginine methyl ester did not affect local responses, but markedly reduced conducted dilation in younger (<64 yr) individuals. Collectively, we show that human coronary arterioles exhibit SK(Ca)/IK(Ca)-mediated hyperpolarization spread through gap junctions, which contributes to conducted vasodilation initiated by focal application of BK. We demonstrate that conducted dilation declines with age, likely due to reduced NO availability, which plays a permissive role in propagating longitudinal vasomotor signaling.